Cytotoxicity And Cell Death Mechanisms Against Cancer Cell Lines Elicited By The Extracts Of Physalis Minima L. - Ooi, Kheng Leong (2009)
the aims of this study were to determine cytotoxicity of some medicinal herbs and to investigate cell death mechanism elicited by the most potent extract as well as its fractions. Tujuan kajian ini ialah untuk menentukan sitotoksisiti beberapa tumbuhan ubatan dan untuk menyelidiki mekanisma kematian sel yang dielisitkan oleh ekstrak yang paling poten dan fraksinya